A Review of Onoceranoids from the Lansium and Lycopodium Genera: Phytochemistry and Their Biological Activities - Septiyanti, Rika; Maharani, Rani; Nafiah, Mohamad Azlan; Mayanti, Tri (Trends in Sciences, 2025)
Onoceranoids, a subgroup of triterpenoids, have demonstrated considerable potential in medical applications due to their diverse biological activities. They exhibit antioxidant, cytotoxic, antimutagenic, antibacterial and antifeedant properties. This study aimed to review the phytochemical composition and biological activities of onoceranoids found in the Lansium and Lycopodium genera. The chemical structures, biological activities, and plant species serving as sources of onoceranoids are analyzed, emphasizing their potential applications in medicine and implications for future research. Experimental approach: Relevant scientific literature on onoceranoids was collected from databases including SciFinder, Google Scholar, and PubMed, covering research from 1967 to 2025. Fifty onoceranoid compounds were identified and analyzed to determine their biological activities and distribution among plant species. The analysis from this review that 96% onoceranoid compounds were found in the Lansium genus, establishing these compounds as marker constituents of this genus. Onoceranoids demonstrate extensive biological potential due to their multifunctional bioactivities. These findings support further research on onoceranoid compounds, including their structural modification and potential therapeutic applications in medicine. HIGHLIGHTS Onoceranoids, a subgroup of triterpenoids, exhibit a wide range of biological activities, including antioxidant, cytotoxic, antimutagenic, antibacterial, and antifeedant properties. This review focuses on the phytochemical composition and biological activities of onoceranoids found in the Lansium and Lycopodium genera. From this review 96 percent of the identified onoceranoid compounds were isolated from the Lansium genus, establishing them as chemical markers for this genus. A total of 50 onoceranoid compounds were identified and analyzed from scientific literature spanning 1967 to 2025. The multifunctional bioactivities of onoceranoids highlight their promising potential for therapeutic applications and future structural modification studies. GRAPHICAL ABSTRACT